Identifying actual and perceived motor competence based profiles among children. Issue 6 (19th March 2022) - Lawson, Chelsey; Eyre, Emma L.J; Tallis, Jason; Watts, Matt; Duncan, Michael J.
ABSTRACT: This study aimed to develop motor competence (MC) profiles in children based on their actual and perceived MC, and to investigate differences in physical activity (PA) behaviour and motivation towards PA between profiles. Two hundred and sixteen British children (7–10 years) took part in this study. Perceived motor competence (PMC) was assessed using the pictorial scale of movement competence. MC was assessed using process-oriented and product-oriented measures. A validated questionnaire assessed motivation towards PA and an objective measure of PA was employed. K-means cluster analysis was used to create profiles. Differences in PA and motivation towards PA were examined using ANCOVAs. Four groups of divergent and convergent levels were identified based on the contribution of either product or process MC with PMC. Motivation towards PA differed by profiles that included actual-process and PMC. Children with high actual process and high PMC had significantly higher levels of autonomous motivation than children with high actual process but low PMC. No significant differences were found between PA levels and profiles. Developing the quality and execution of actual motor competence (AMC) and PMC is key to stimulate motivation towards PA. Furthermore, maintaining AMC and PMC simultaneously may be imperative to children's future PA behaviour.